Explaining Economic Inequality Using the Film, The Queen of Versailles - Booker, Teresa A. (Radical Teacher, 2019)
In introductory classes on race and ethnicity, terms like wealth, economic inequality, and SES (socio-economic status) often take center stage during one chapter or another. There are numerous text books on this subject. But, I’ve had more success explaining these terms by using different media. To illustrate such important themes to non-economics majors, I often show and discuss The Queen of Versailles, a 2012 documentary that depicts the Siegel family’s 2-year meteoric decent from wealth (being worth billions of dollars) to rags (being worth “only” tens of millions of dollars).